Gaming under the influence: An exploratory study - Škařupová, Kateřina; Blinka, Lukas; Ťápal, Adam (Journal of behavioral addictions, 2018)
Background and aims Association between substance use and excessive play of online games exists both in theory and research. However, no study to date examined playing online games under the influence of licit and illicit drugs. Methods We questioned a convenient online sample of 3,952 Czech online gamers on their experiences and motives of using caffeine, alcohol, tobacco, psychoactive pharmaceuticals, and illicit drugs while playing massive multiplayer online games (MMOGs). Results The results showed low prevalence of illicit drug use while playing online games. Substance use was positively associated with intensity of gaming and both addiction and engagement; psychoactive substances with stimulating effect were linked to higher engagement and gaming intensity, whereas use of sedatives was associated with higher addiction score. Substance use varied slightly with the preference of game genre. Discussion Drug use while playing appears as behavior, which is mostly not related to gaming - it concerns mostly caffeine, tobacco, alcohol, or cannabis. For some users, however, drug use was fueled by motivations toward improving their cognitive enhancement and gaming performance.
Keywords: Male; lidé středního věku; Prevalence; návykové chování; Surveys and Questionnaires; Substance-Related Disorders; Humans; Middle Aged; mužské pohlaví; prevalence; Female; mladiství; Behavior, Addictive; online gaming; ženské pohlaví; substance use; průzkumy a dotazníky; internet; mladý dospělý; Adult; videohry; Longitudinal Studies; Young Adult; Internet; addiction; Adolescent; longitudinální studie; dospělí; dítě; lidé; Video Games; poruchy spojené s užíváním psychoaktivních látek; engagement; Child